Peran Professional Commitment terhadap Subjective Career Success pada Guru - Muhammad Taufik Kautsar; Tri Muji Ingarianti; Devina Andriany (UIN Sunan Kalijaga, 2022)
Every teacher dreams of a successful and sustainable career to achieve satisfaction in their career. Even though teachers' career is guaranteed, teachers are still worried about their career success, especially about their subjective success. Subjective career success is defined as an individual's subjective perspective, assessment, and satisfaction with his/her career achievement. Professional commitment is loyalty to their profession, and positive evaluation of the profession, so that it is considered to have a role in achieving subjective career success. The objective of this research was to examine the role of professional commitment on subjective career success in teachers. Using a non-experimental correlational quantitative approach this research has 320 teachers as the subject. The measuring instrument used was Professional Commitment Scale and Subjective Career Success Inventory, with the sampling technique used was accidental sampling. The data analysis method used a simple regression test to determine the correlation between variables and a multiple regression test to determine the per dimension role. The research results indicated the role of professional commitment on subjective career success. It is hoped that the results of this study can be considered in increasing teacher commitment to their profession to increase subjective career success. Abstrak. Setiap guru memimpikan karier yang sukses dan berkelanjutan agar mendapatkan kepuasan dalam kariernya. Meskipun berkarier menjadi seorang guru begitu terjamin, namun seorang guru tetap merasakan kekhawatiran akan kesuksesan kariernya, terkhusus pada kesuksesan subjektifnya. Subjective career success didefinisikan sebagai perspektif subjektif individu, penilaian, dan kepuasan terhadap pencapaian kariernya. Professional commitment merupakan loyalitas terhadap profesi, dan evaluasi positif pada profesi, sehingga dianggap mampu berperan dalam mencapai subjective career success. Tujuan dari penelitian ini yaitu untuk mengetahui peran professional commitment terhadap subjective career success pada guru. Menggunakan pendekatan kuantitatif korelasional non-eksperimen dengan subjek penelitian yaitu 320 guru. Alat ukur yang digunakan yaitu Professional Commitment Scale dan Subjective Career Success Inventory, dengan teknik sampling yang digunakan yaitu accidental sampling. Metode analisis data menggunakan uji regresi sederhana untuk mengetahui peran antar variabel dan uji regresi berganda untuk mengetahui peran per dimensi. Hasil penelitian ini menunjukan adanya peran professional commitment terhadap subjective